Correlates of physical activity and sedentary time in young adults: the Western Australian Pregnancy Cohort (Raine) Study - Erin K. Howie; Joanne A. McVeigh; Elisabeth A. H. Winkler; Genevieve N. Healy; Romola S. Bucks; Peter R. Eastwood; Leon M. Straker (BMC, 2018)
Abstract Background The socioecological model proposes a wide array of factors that influence behaviours. There is a need to understand salient correlates of these activity behaviours in a specific population. However, few studies identified socio-demographic, behavioural, physical, and psychological correlates of objectively-assessed physical activity and sedentary time in young adults. Methods This was a cross-sectional analysis of participants in the Raine Study (a pregnancy cohort started in 1989). Australian young adults (mean 22.1 years ± SD 0.6) wore Actigraph GT3X+ accelerometers on the hip 24 h/day for seven days to assess moderate-to-vigorous physical activity (MVPA) and sedentary time (n = 256 women, n = 219 men). Potential correlates were assessed via clinical assessment and questionnaire and included socio-demographic variables (ethnicity, relationship status, work/study status, education, mothers education), health behaviours (food intake, alcohol consumption, smoking status, sleep quality), and physical and psychological health aspects (anthropometrics, diagnosed disorders, mental health, cognitive performance). Backwards elimination (p < 0.2 for retention) with mixed model regressions were used and the gender-stratified analyses were adjusted for demographic variables, waking wear time and number of valid days. Results Increased time spent in MVPA was associated with: being single (IRR 1.44 vs in a relationship living together, 95%CI: 1.17, 1.77, p = .001) in women; and better sleep quality in men (lower scores better IRR 0.97, 95%CI: 0.93, 1.00). Less time spent sedentary was associated with: lower mother's education (− 32.1 min/day, 95%CI -52.9, 11.3, p = 0.002 for having mother with no university degree vs at least a baccalaureate degree) and smoking (− 44.3 min/day, 95%CI: - 72.8, − 15.9, p = .0002) for women; lower education status (− 32.1 min/day, 95%CI: -59.5, − 4.8, p = 0.021 for having no university degree vs at least a baccalaureate degree) and lower depression scores in men (− 2.0, 95%CI: - 3.5, − 0.4, p = 0.014); more alcoholic drinks per week for women (− 1.9 min/day, 95%CI: -3.1, − 0.6, p = 0.003) and men (− 1.0, 95%CI: -1.8, − 0.3, p = 0.007). Conclusions Less desirable correlates were associated with positive levels of activity in young Australian adult women and men. Interventions to increase MVPA and decrease sedentary activity in young adults need to specifically consider the life stage of young adults.